Determining the reflective thinking skills of pre-service teachers in learning and teaching process - Gurol, Aysun (Sila Science, 2011)
In today's education process the mode of thinking which would be used in solving the vital problems is the reflective thinking for both teachers and students. In this study it is aimed to determine the reflective thinking skills of pre-service teachers in learning and teaching process. The study is configured in depictive and survey model. Two hundred and thirty tree pre-service teachers, one hundred of them women and one hundred and thirty three of them pre-service teachers, participated in the study. As a result of the study, it emerges that the reflective thinking is an indispensable mode of thinking for the education of the teacher. Besides it is determined that the pre-service teachers often act according to the reflective thinking.
Keywords: Critical thinking; Learning; Reflective thinking